Mechanics of composite materials - Christensen, R. M. (Dover Publications, 2005)
Graduate-level text assembles, interprets, and interrelates contributions tofield of composite materials from theoretical research, lab developments, and product applications.Focuses on continuum mechanics aspects of behavior; specifically, it invokes idealized geometric models of heterogeneous system fortheoretical predictions of macroscopic properties in terms of individual constituent materials. 1979 edition.
Reprint. Originally published: New York : Wiley, 1979.
Keywords: Composite materials -- Mechanical properties.; elektronické knihy; electronic books